Foreign Language Education in China: When Reforms Meet Tradition - Yue Peng (Canadian Society for Studies in Education, 2018)
Abstract: Previous research has identified a discrepancy between intended pedagogical reforms and the reality of implementing them in the classroom, particularly for teaching English as a second language in China. The distinction between the conceptual foundation behind Communicative Language Teaching (CLT) and dominant local educational principles has been used to explain the difficulty of implementing reform. To gain a deeper understanding of the conceptual constraints on reform, this article describes the Deweyan educational principles behind CLT and the Confucian educational values that underpin the dominant language teaching approach in China. This article also provides a historical perspective of how the two streams of educational ideas have co-existed and interacted in Chinese education in general and in foreign language teaching in particular. This conceptual analysis and historical review provides a deeper understanding of the current status of English language teaching in China and the conceptual constraints on reform.